Photonanozyme–Kras–ribosome combination treatment of non-small cell lung cancer after COVID-19 - Si, Qiaoyan; Bai, Mingjian; Wang, Xiaolong; Wang, Tianyu; Qin, Yan (Frontiers in Immunology, 2024)
With the outbreak of the coronavirus disease 2019 , reductions in T cell function and exhaustion have been observed in patients post-infection of COVID-19. T cells are key mediators of anti-infection and antitumor, and their exhaustion increases the risk of compromised immune function and elevated susceptibility to cancer. Non-small cell lung cancer (NSCLC) is the most common subtype of lung cancer with high incidence and mortality. Although the survival rate after standard treatment such as surgical treatment, and chemotherapy, has improved, the therapeutic effect is still limited due to drug resistance, side effects, and recurrence. Recent advances in molecular biology and immunology enable the development of highly targeted therapy and immunotherapy for cancer, which has driven cancer therapies into individualized treatments and gradually entered clinicians' views for treating NSCLC. Currently, with the development of photosensitizer materials, phototherapy has been gradually applied to the treatment of NSCLC. This review provides an overview of recent advancements and limitations in different treatment strategies for NSCLC under the background of COVID-19. We discuss the latest advances in phototherapy as a promising treatment method for NSCLC. After critically examining the successes, challenges, and prospects associated with these treatment modalities, their profound prospects were portrayed.